Návrh změn systému odměňování zaměstnanců ve vybrané společnosti - Rous, Filip (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Smyslem této bakalářské práce je vytvoření návrhu změn systému odměňování zaměstnanců ve společnosti FORTYS PIZZA s.r.o. První část pojednává o teoretických poznatcích z oblasti odměňování zaměstnanců. Druhá část se zabývá analýzou současného stavu systému odměňování zaměstnanců ve společnosti a vnitřních a vnějších vlivů ovlivňujících tento systém odměňování a třetí závěrečná část obsahuje navržené změny v systému odměňování zaměstnanců.

The aim of this bachelor thesis is to create a proposal for changes in the system of remuneration of employees in company FORTYS PIZZA s.r.o. The first part deals with the theoretical knowledge of remuneration of employees. The second part includes the analysis of current status of remuneration employees in the company and internal and external factors affecting this system of remuneration. The third final part contains proposals changes in the system of remuneration employees.
Proposal for Changes to the System of Remuneration of Employees in the Selected Company
Keywords: Mzda; benefity; zaměstnanec; odměňování zaměstnanců; celková odměna; Wage; benefits; employee; employee remuneration; total reward